Generation of a high-resolution genetic map and a YAC contig of the Lurcher locus on mouse chromosome 6. - Zuo, J; De Jager, P L; Norman, D J; Heintz, N (Genome Research, 1995)
Lurcher (Lc) is a semidominant mouse mutant that displays progressive neurodegeneration during perinatal development. This genetic lesion results in apoptotic neuronal death in a dosage dependent and cell autonomous manner in specific neurons during their terminal differentiation. To understand the molecular basis of the Lc mutation, we have adopted a positional cloning approach based on its location on mouse chromosome 6. To define the Lc locus, we have extended our previous analysis of an intersubspecific backcross between Mus m. castaneus and B6CBACa-Aw-j/A-Lc consisting of 504 animals (Norman et al. 1991). In addition, 580 animals of a generic backcross between Mus spretus and C57BL/6 (The European Collaborative Interspecific Backcross) were utilized for the fine genetic mapping of the Lc locus. Using three RFLP markers and nine microsatellite markers in the vicinity of the Lc locus, we determined the order and relative genetic distances of these markers at a resolution of 0.1 cM. The Lc mutation was mapped between two flanking markers, D6Mit121 and D6Mit175, separated by a genetic distance of 0.5 cM. We then initiated the cloning of the genomic region surrounding these two markers by screening a YAC library and characterizing YAC end sequences for further screening. This effort has resulted in the construction of a YAC contig consisting of 14 YACs and spanning a 3-Mb region. Markers isolated from these YACs were used to further define the Lc locus, resulting in a physical map that places the Lc gene within an estimated 300-kb interval. This set of YACs and markers will serve as DNA sources for the identification of the Lc gene.